2016
DOI: 10.1002/rev3.3061
|View full text |Cite
|
Sign up to set email alerts
|

Feedback effectiveness in professional learning contexts

Abstract: Assessment organisations that operate at a national level in the UK employ hierarchic assessor monitoring arrangements, where the most senior assessors (known as team leaders) feedback to assessors in their teams on their marking performance. According to a sociocultural viewpoint, this feedback possesses learning potential as it allows assessors insights into the perspectives of their team leader. There is relatively little research on feedback effectiveness in professional assessment contexts. To gain insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 158 publications
0
9
0
Order By: Relevance
“…In the Phase 1 literature, ten papers connected virtual learning pedagogies with cognitive exchange (Bosley and Young, 2006; Donnelly, 2013; Bellandi and Depropris, 2021; Caspi and Blau, 2008; Duffett, 2015; Hernández-Sellés et al, 2020; Guo et al, 2021; Penman and Lai, 2003; Peacock and Cowan, 2017; Johnson, 2016). This demonstrated that pedagogic choice could influence cognitive exchange.…”
Section: Literature Review Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…In the Phase 1 literature, ten papers connected virtual learning pedagogies with cognitive exchange (Bosley and Young, 2006; Donnelly, 2013; Bellandi and Depropris, 2021; Caspi and Blau, 2008; Duffett, 2015; Hernández-Sellés et al, 2020; Guo et al, 2021; Penman and Lai, 2003; Peacock and Cowan, 2017; Johnson, 2016). This demonstrated that pedagogic choice could influence cognitive exchange.…”
Section: Literature Review Strategymentioning
confidence: 99%
“…Not all dialogic interactions between a teacher and student lead to cognitive exchange. Monologic exchange does not necessarily cause transfer (Mukhametzyanova, 2021) because feedback may be nonexistent or ineffective (Johnson, 2016). When learning, cognitive exchange may involve a teacher imparting information and a student appropriating knowledge (Dubiner, 2010), but it does not have to.…”
Section: Cognitive Exchange In Higher Degree Visual Art Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a webcam that is turned off makes it difficult for the instructor to provide timely and constructive feedback (Racheva, 2018 ). Note that research shows that effective feedback is an essential component of learning (Johnson, 2016 ; Winstone & Carless, 2019 ). For example, without a webcam, it is impossible to provide spontaneous non-verbal behavioral feedback, which is a widely used and successful strategy in face-to-face instruction (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in accordance with previous studies on the characteristics of effective feedback provided to students, such as being timely and enabling dialogues with students (Carless, 2015), and potential barriers to feedback, such as negative perceptions of the inaccuracy and irrelevance of the feedback provided which might lead to rejection due to lack of trust (Boud & Molloy, 2013). Furthermore, these findings were broadly aligned with the four core factors of language, content, timing and form, each of which is related to the effectiveness of feedback in hierarchic professional contexts (Johnson, 2016). For example, the examiners indicated that the structured feedback reports were well-organised and that the language used was easy to understand.…”
Section: Rqmentioning
confidence: 92%